CREATION OF EXPORT-ORIENTED NETWORK OF GRAIN ELEVATORS IN UKRAINE - Kozachenko, D. M.; Vernigora, R. V.; Rustamov, R. S. (Science and Transport Progress, 2017)
Purpose. The scientific paper highlights improving the efficiency of export rail transportation of grain cargoes in Ukraine by introducing shipper routing and concentration of loading at the terminal grain elevators. Methodology. According to the experience of the USA and Canada, one of the most effective ways to reduce costs in the grain to-port supply chain is a shipper routing of the rail traffic. Shipper routing for transportation of grain cargoes involves the concentration of their loading on the multiple junctions. The junctions are proposed to be selected with the use of cluster analysis methods. For the formation of the grain loading concentration areas the authors used methods of set theory and multi-criteria optimization. Findings. Based on agglomerative cluster analysis algorithm, the junctions on a network of Ukrainian railways are selected and the areas of possible concentration of grain loading are formed. DSU-algorithm allowed distinguishing the overlapping and non-overlapping areas of concentration. The problem of selecting non-overlapping areas of the grain loading concentration is formalized as the problem of multiobjective integer programming with boolean variables. The solution of this problem by a modified simplex algorithm allows selecting on the railway network of Ukraine 24 districts of possible grain loading concentration, which cover 70 stations and at minimal additional cost provide routing of about 7.5 million tons of grain per year. Originality. The originality of the work lies in the fact that the authors developed the mathematical procedure for selection of junctions and concentration areas of grain loading at the Ukrainian railway network, taking into account the economic efficiency of the process. Practicalvalue. Application of the developed method of grain loading concentration for the formation of unit trains will significantly reduce the logistics costs in the supply chain of grain to Ukrainian ports for export and, consequently, increase its competitiveness in foreign markets.